'Who owns our schools?' An analysis of the governance of free schools in England. (May 2014) - Higham, Rob
The legal basis of free schools, provided for in the Academies Act 2010, allows the Secretary of State for Education 'to enter into Academy arrangements with any person'. A range of debate has ensued over who will govern free schools. This article develops an analysis of the individuals and organizations that have had free school proposals accepted by government. The article progresses, first, by locating free schools in the existing policy trajectories towards privatization and self-governing schools. Second, it draws on a mapping exercise and interviews with a sample of 58 free school proposers, sponsors and suppliers to explore the processes through which free schools are established. The main categories of free school proposers are identified as: local civil society groups; sponsoring organizations; existing educational institutions. Third, the article considers the wider implications for school governance. It is argued free school policy allows governance to become an additional and direct lever through which those with the capacity to do so are able to mould state education in their own interests.